Analysis of The Makharijul Letter Qalqalah in Surah Al Falaq in High School Students at Aisyiyah Boarding School Bandung - Akbar Pilayati; Lina Marlina (Tilawah: Journal of Al-Qur'an Studies, 2025)
This study aims to analyze the pronunciation ability of 10th grade students at SMA ‘Aisyiyah Boarding School Bandung in articulating the qalqalah letters in Surah Al-Falaq based on the theory of makhārijul ḥurūf. The research employed a descriptive qualitative approach with data collected through observation, audio recordings, and interviews. The findings reveal that only some students were able to pronounce qalqalah letters correctly in accordance with their articulation points and phonetic characteristics. Common pronunciation errors included the absence of sound rebound, overly weak or excessive articulation, incorrect articulation points, and the inability to distinguish between qalqalah ṣughrā and kubrā. Contributing factors to these errors were the lack of phonetic awareness, minimal talaqqī and musyāfahah practice, and limited learning media. This study recommends the use of a more phonetics-based and practical tajwid teaching approach to improve students’ Qur’anic recitation quality.